Minat Beli: Peran Citra Merek yang Dipersepsikan oleh Konsumen Produk Otomotif - Ramadhani, Ulfha; Wibowo, Lili Adi; Widjajanta, Bambang (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2019)
This study aims to reveal the brand image and purchase interest in Daihatsu Terios in Indonesia. This study used a descriptive approach with explanatory survey method. The unit of analysis in this study is prospective consumers Daihatsu Terios in Indonesia as many as 120 orang.Teknik collecting data field study questionnaires. The data analysis technique used is descriptive technique using frequency distribution. Research findings showed that the image of the brand image are in the good category and description buying interest in the excellent category. Differences in this study lies in the object of research, study time, measuring tools, literature used, the theory used and the results of researchswitching barriers and customer loyalty.